The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7ob02117h
|View full text |Cite
|
Sign up to set email alerts
|

On the regiochemical differences between Pd-catalyzed heterocyclization–allylation and –arylation reactions of alkynylbenzamides: preparation of 4-allyl-isochromen-1-imines and computational study

Abstract: The Pd(0)-catalyzed cyclization-allylation reactions of 2-alkynylbenzamides proceed with high regioselectivity to afford the 6-endo-cyclization-derived products 4-allyl-isochromen-1-imines. DFT calculations have been performed on this and the related arylation reaction, that has been reported to afford the products corresponding to an exo-cyclization under similarly Pd(0)-catalyzed conditions. Under the reaction conditions, these cyclizations are presumed to be triggered by activation of the C-C triple bond wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Two pathways are then possible depending on whether alkyne C–H palladation precedes or follows the heterocyclization event. For example, pathway A, where cyclization precedes the C–H palladation step, has been reported to be followed by the aminocyclization–alkynylation reactions of 2-alkynyldimethylaniline derivatives, whereas pathway B would be reminiscent of the mechanism followed by typical Pd(0)-catalyzed reactions such as arylations, where the initial oxidative addition of an aryl halide provides the Pd­(II) species needed to activate the C–C triple bond and trigger heterocyclization. ,− ,, Interestingly, we have recently found that, in the particular case of arylations (and allylations) of 2-alkynylbenzamides, the final regiochemical outcome is partially determined by the character of the R group (aryl or allyl) in the organopalladium­(II) RPdY σ complex intermediate …”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…Two pathways are then possible depending on whether alkyne C–H palladation precedes or follows the heterocyclization event. For example, pathway A, where cyclization precedes the C–H palladation step, has been reported to be followed by the aminocyclization–alkynylation reactions of 2-alkynyldimethylaniline derivatives, whereas pathway B would be reminiscent of the mechanism followed by typical Pd(0)-catalyzed reactions such as arylations, where the initial oxidative addition of an aryl halide provides the Pd­(II) species needed to activate the C–C triple bond and trigger heterocyclization. ,− ,, Interestingly, we have recently found that, in the particular case of arylations (and allylations) of 2-alkynylbenzamides, the final regiochemical outcome is partially determined by the character of the R group (aryl or allyl) in the organopalladium­(II) RPdY σ complex intermediate …”
Section: Resultsmentioning
confidence: 53%
“… a wB97XD/LANL2DZ/6-31G*//wB97XD-SMD (DMF)/LANL2DZ/6-31G*. b Data taken from ref . c Agostic interaction with C–H from AcO Me group. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrigued by these interesting chemo-and regioselectivities, we here performed a comparative theoretical study on the four reactions shown in Scheme 2, aiming at a better understanding of the intrinsic molecular mechanism of catalyst-dependent divergent reactivities. It is noted that Aurrecoechea and coworkers 26,27 have reported two excellent theoretical works on the origin of the chemo-and regioselectivity of intramolecular annulations of o-alkynylbenzamides, which are very enlightening for the present mechanism study. In this work, we calculated the reactions catalyzed by all four catalysts shown in Scheme 2; however, the results for the Na 2 CO 3 -catalyzed system are shown in the Supporting Information (pages S9− S12) due to the intrinsically different mechanism by base from that by transition metals.…”
Section: Introductionmentioning
confidence: 84%